2009
DOI: 10.4103/0973-3930.54286
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in diabetes management with particular reference to India

Abstract: Diabetes was estimated to be responsible for 109 thousand deaths, 1157 thousand years of life lost and for 2263 thousand disability adjusted life years (DALYs) in India during 2004. However, health systems have not matured to manage diabetes effectively. The limited studies available on diabetes care in India indicate that 50 to 60% of diabetic patients do not achieve the glycemic target of HbA1c below 7%. Awareness about and understanding of the disease is less than satisfactory among patients, leading to del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
41
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(44 citation statements)
references
References 37 publications
(32 reference statements)
3
41
0
Order By: Relevance
“…Available literature suggests that the management of diabetes in India is sub-optimal for the majority of patients. Only 40-50% of individuals achieve the target for glycemic control, while lower numbers achieve targets for blood pressure and lipid control [5,28,33,34,40].…”
Section: Introductionmentioning
confidence: 99%
“…Available literature suggests that the management of diabetes in India is sub-optimal for the majority of patients. Only 40-50% of individuals achieve the target for glycemic control, while lower numbers achieve targets for blood pressure and lipid control [5,28,33,34,40].…”
Section: Introductionmentioning
confidence: 99%
“…Many LMICs, particularly in rural settings, lack the personnel and properly equipped clinics needed to provide specialized care [31,32]. Additionally, public awareness of diabetes status and management is low, and many clinics and patients cannot afford diabetes treatment [33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…The population level prevalence of hypertension and diabetes in adults in India is high, with estimates of 23% [2] and 8.7% [3] respectively. However, studies have shown that management of hypertension, cardiovascular disease, and diabetes at primary care level is suboptimal [4–7], and only half of the patients achieve their target blood pressure and blood sugar level, which increases their risk for CVD events [4,5]. Some of the challenges in treating and managing chronic conditions are suboptimal adherence to management guidelines by the physicians [5,8], lack of regular patient monitoring and undiagnosed comorbidities such as anxiety, depression, and alcohol use disorders which can contribute to failure to follow treatment plans [911].…”
Section: Introductionmentioning
confidence: 99%
“…However, studies have shown that management of hypertension, cardiovascular disease, and diabetes at primary care level is suboptimal [4–7], and only half of the patients achieve their target blood pressure and blood sugar level, which increases their risk for CVD events [4,5]. Some of the challenges in treating and managing chronic conditions are suboptimal adherence to management guidelines by the physicians [5,8], lack of regular patient monitoring and undiagnosed comorbidities such as anxiety, depression, and alcohol use disorders which can contribute to failure to follow treatment plans [911]. Mobile health (mHealth) technologies are being advocated to strengthen the health system, and systematic reviews have shown that an mHealth-based Clinical Decision Support System (CDSS) improves preventive care and the physician’s clinical decision quality in hypertension and diabetes management [8] although the evidence on their effects on cardiovascular outcomes is limited [12].…”
Section: Introductionmentioning
confidence: 99%